Molecular epidemiology of extended-spectrum beta-lactamases and carbapenemases-producing Shigella in Africa: a systematic review and meta-analysis - Namwin Siourimè Somda; Rabbi Nyarkoh; Abel Tankoano; Ouindgueta Juste Isidore Bonkoungou; Patience B. Tetteh-Quarcoo; Eric S. Donkor (BMC Infectious Diseases)
Abstract Background The treatment of Shigella infections has become a major challenge due to the emergence of multidrug-resistant Shigella. There is however insufficient knowledge regarding the molecular epidemiology of Shigella strains producing beta-lactamases in Africa. This systematic review investigated the scientific literature on the molecular epidemiology of extended-spectrum beta-lactamase (ESBL) and carbapenemases producing Shigella in Africa. Methods Papers published in English and French from African countries on the molecular epidemiology of ESBL and carbapenemase producing Shigella from January 1999 to July 5, 2024 were reviewed. An extensive literature search was conducted through electronic databases including PubMed, Scopus, Web of Sciences, African Journals Online (AJOL) and Google scholar using specific keywords. The meta-analysis and forest plots of Shigella species, ESBL and carbapenemases genes were done using the comprehensive Meta-Analysis software. All data were analyzed using a binary random-effects model by the DerSimonian-Laird method at a 95% confidence interval. Results Out of the 583 research articles, only 18 (3.1%) articles representing eleven countries were included in the meta-analysis. The overall pooled prevalence of ESBL and Carbapenem Resistant (CR)-producing Shigella was estimated as 41.2% (95% CI: 22.8–62.4; I2 = 93.7%, p < 0.05). The leading ESBL and CR-producing Shigella species reported in this review was Shigella flexneri, 34.5% (95% CI: 16.6–58.2; I2 = 94.9%, p < 0.05). ESBL and CR-producing Shigella sonnei was the least reported with estimated prevalence of 6.7% (95% CI: 3.4–13.2; I2 = 80.7%, p < 0.05). In this review, bla TEM , bla OXA−1 , and bla CTX−M were the most prevalent genes in Africa with prevalence of 25.9% (95% CI: 13.9–43.2; I2 = 90.9%, p < 0.05), 25.7% (95% CI: 14.9–43.0; I2 = 93.7%, p < 0.05), and 10.8% (95% CI: 4.5–23.4; I2 = 85.6%, p < 0.05) respectively. The prevalence of Carbapenemases genes on the other hand was low, reported as 0.8% (95% CI: 0.2–10.3; I2 = 51.4%; p < 0.05) for bla NDM , 1.1% for bla KPC , and 0.5% for bla IMP . Conclusion This study highlighted Shigella flexneri as the most prevalent ESBL and CR-producing Shigella species found in various African countries. The findings from this review indicate bla TEM , bla OXA−1 and bla CTX−M as the most prevalent genes in Africa while carbapenemases are least prevalent. The findings from the study suggest that ESBL and CR-producing Shigella pose a significant public health threat in Africa. Effective antimicrobial resistance (AMR) surveillance strategies are needed to improve the management and treatment of Shigella infections in Africa.